INTERETHNIC ASSOCIATIONS OF INCREASED HEART RATE AS A FACTOR OF CARDIOVASCULAR RISK. PART 2: GENETIC MARKERS - T. A. Mulerova; M. Yu. Ogarkov (Евразийский Кардиологический Журнал, 2021)
Purpose. To study the genetic aspects of increased heart rate (HR) in representatives of various ethnic groups living in Mountain Shoria. Material and Methods. The study involved residents of the villages of Mountain Shoria aged 18 years and older. Included are 901 people – representatives of indigenous nationality (Shors), 408 people – of nonindigenous nationality. The groups did not differ by gender and age. The analysis was carried out depending on the increased level of heart rate (over 80 beats/min). Typing of polymorphic sites of the ACE (I/D, rs4340), ADRB1 (p.145A> G, Ser49Gly, rs1801252), ADRA2B (I/D, rs28365031), MTHFR (c.677C> T, Ala222Val, rs1801133) and NOS3 (VNTR, 4b/4a) was carried out using polymerase chain reaction. The association of different genotypes with heart rates above 80 beats/min was judged by the odds ratio in five inheritance models (codominant, dominant, recessive, overdominant and log-additive), and its 95% confidence interval was calculated. Results. Ethnic features of the prevalence of increased heart rate have been established depending on the polymorphism of candidate genes involved in the pathogenesis of arterial hypertension. The respondents of the indigenous ethnic group had a high probability of developing tachycardia determined by the carriage of the C/T genotype of the MTHFR gene according to an overdominant type of inheritance [OR = 2.46]. Allele D of the ACE gene determined the tendency to the development of this pathology according to the recessive type of inheritance [OR = 1.91]. However, among young people and men, carriage of a prognostically unfavorable D/D genotype of this gene was associated with a high risk of increased heart rate [OR = 3.34] and [OR = 4.62], respectively. In a cohort of non-indigenous nationality, the heterozygous genotype I/D of the ACE gene determined the likelihood of tachycardia by an overdominant type of inheritance [OR = 2.08]. Conclusions. Most epidemiological studies show a significant difference in the contribution of the studied polymorphisms to the appearance of increased heart rate for various ethnic groups. For a small population of Mountain Shoria, genetic features of the development of tachycardia have been established. In this regard, it is advisable to take into account national characteristics when determining individual risk, and apply personalization to correction programs.